Solar irradiance availability based on bratislava measurements (2019)
Climate changes can be observed in last decades evidently. Generally, temperature and sunshine are rising also in countries located in higher geographical latitudes. These facts have impact on the design building constructions and indoor environment. Sun with its direct radiation is basic source of energy on the Earth and has important influence on visual task performance and application of shading devices in building apertures to avoid overheating and glare phenomena. The precise measurements of global, direct and diffuse irradiances are carried out in Bratislava at the Institute of Construction and Architecture Slovak Academy of Sciences with cooperation of Solargis Ltd. Bratislava. These data, after quality control processing, are the basis of the irradiance availability research. Applied methods for data evaluation and determination of for solar irradiance availability are based on the statistical procedures. Paper presents results of experimental solar irradiance measurements provided in Bratislava, determination of direct solar irradiance availability and discusses importance of solar irradiance availability in point of view of the building environmental quality and building design.